2010
DOI: 10.1074/jbc.m110.131995
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Imprinted Dlk1-Dio3 Region Correlates with Pluripotency Levels of Mouse Stem Cells

Abstract: Low reprogramming efficiency and reduced pluripotency have been the two major obstacles in induced pluripotent stem (iPS) cell research. An effective and quick method to assess the pluripotency levels of iPS cells at early stages would significantly increase the success rate of iPS cell generation and promote its applications. We have identified a conserved imprinted region of the mouse genome, the Dlk1-Dio3 region, which was activated in fully pluripotent mouse stem cells but repressed in partially pluripoten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
226
1
3

Year Published

2011
2011
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(242 citation statements)
references
References 23 publications
11
226
1
3
Order By: Relevance
“…Epigenetically, the locus is fully methylated in many iPSC lines, while some lines have only one allele silenced, as is the case in ESC. Functionally, it seems that iPSC with the Dlk1-Dio3 locus fully silenced can not form tetraploid complementation animals, and chimerism is also significantly lower when doing blastocyst injections, when compared with ESC [10,30].…”
Section: Transcriptional Comparison Of Esc and Ipscmentioning
confidence: 99%
“…Epigenetically, the locus is fully methylated in many iPSC lines, while some lines have only one allele silenced, as is the case in ESC. Functionally, it seems that iPSC with the Dlk1-Dio3 locus fully silenced can not form tetraploid complementation animals, and chimerism is also significantly lower when doing blastocyst injections, when compared with ESC [10,30].…”
Section: Transcriptional Comparison Of Esc and Ipscmentioning
confidence: 99%
“…Studies from Stadtfeld et al [20] and Liu et al [18] showed that the imprinted Dlk1-Dio3 region is mostly silenced by DNA methylation in OSKM-induced iPSCs and that the activation of this imprinted region might actually correlate with the degree of iPSC pluripotency. To probe the potential effect of miR-29b on the activation of the Dlk1-Dio3 region, we analyzed the expression of the genes and miRNAs in the Dlk1-Dio3 region in both OSKM-derived iPSC lines and OSKM + miR-29b-derived iPSC lines.…”
Section: Mir-29b-dnmt Signaling Is Involved In Regulating Met and Thementioning
confidence: 99%
“…Treatment of cells with 5-Aza-2'-deoxycytidine (AZA, a non-specific inhibitor of DNMTs) facilitates the transition from somatic cells to pluripotent stem cells [14][15][16], and DNA demethylation is required for the reactivation of epithelial genes in the MET process at the early stage of iPSC generation [17]. Recent studies have found that the activation of certain imprinted regions, such as the Dlk1-Dio3 locus, is correlated with the developmental potential of fully pluripotent iPSCs [18,19]. Aberrant DNA hypermethylation might be the major cause of the Dlk1-Dio3 region silencing that prevents cells from be-coming fully pluripotent iPSCs [18,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…S7A) [17]. We also examined the expression of imprinting genes, as a close relationship between iPSC quality, and these genes were recently suggested [25,26]. Nevertheless, no significant reduction in the expression of imprinting genes between 3F-iPSCs, 4F-iPSCs, or control ES cell lines was observed except for the 2A-3F-4-iPSC clone in which the expression of the Gtl2, Rtl1, Rian, and Mirg genes was suppressed (Supporting Information Fig.…”
Section: Improvement Of 3f-ipscs By Tsamentioning
confidence: 99%